Estimating the Prevalence of Chronic Hepatitis B Virus Infection—New York City, 2008 - France, Anne Marie (Springer US, 2012)
Chronic hepatitis B virus (HBV) infection is a preventable cause of liver failure, cirrhosis, and liver cancer; estimated chronic HBV infection prevalence is 0.3–0.5% in the USA. Prevalence in New York City (NYC) is likely higher because foreign-born persons, who represent 36% of NYC’s population versus 11% nationwide, bear a disproportionate burden of chronic HBV infection. However, because no comprehensive, population-based survey of chronic HBV infection has been conducted in NYC, a reliable prevalence estimate is unavailable. We used two approaches to estimate chronic HBV infection prevalence in NYC: (1) a census-based estimate, combining local and national prevalence data for specific populations, and (2) a surveillance-based estimate, using data from NYC’s Department of Health and Mental Hygiene Hepatitis B Surveillance Registry and adjusting for out-migration and deaths. Results from both the census-based estimate and the surveillance-based estimate were similar, with an estimated prevalence of chronic HBV in NYC of 1.2%. This estimate is two to four times the estimated prevalence for the USA as a whole. According to the census-based estimate, >93% of all cases in NYC are among persons who are foreign-born, and approximately half of those are among persons born in China. These findings underscore the importance of local data for tailoring programmatic efforts to specific foreign-born populations in NYC. In particular, Chinese-language programs and health education materials are critical. Reliable estimates are important for policymakers in local jurisdictions to better understand their own population’s needs and can help target primary care services, prevention materials, and education.